Hemodynamic repercussions of exaggerated lithotomy position for vaginal hysterectomy in cardiac patient. Case report - Bessa Jr., Roberto Cardoso; Silva Filho, Agnaldo L. [UNESP]; Maia, Plínio V.; Quites, Lúcio O.; Triginelli, Sérgio A. (My University, 2006)
BACKGROUND AND OBJECTIVES: Vaginal hysterectomy shortens surgery duration and may be performed with neuraxial block, which promotes better postoperative analgesia and lower systemic response to surgical procedure. This report aimed at describing hemodynamic changes promoted by exaggerated lithotomy position in cardiac patient. CASE REPORT: Female patient, 33 years old, with history of abnormal uterine bleeding and anemia. Ultrasound revealed myomas of approximately 420 cm3. Patient had thrombophilia and dilated cardiomyopathy, with history of two ischemic strokes and two acute myocardial infarction. Monitoring consisted of invasive blood pressure and pulmonary artery catheter for continuous cardiac output measurement. Spinal anesthesia was performed with hyperbaric bupivacaine and morphine. Patient was placed in exaggerated lithotomy position being total hysterectomy performed by the Heaney technique and b i l a t e r a l salpingectomy. Intraoperative intercurrences were post-positioning decreased cardiac output and increased right chambers pressure requiring dobutamine. CONCLUSIONS: Exaggerated lithotomy positionmay promote hemodynamic changes which should be considered when choosing the surgical technique. © Sociedade Brasileira de Anestesiologia, 2006.
Repercussões hemodinâmicas do posicionamento em litotomia exagerada para histerectomia vaginal em paciente cardiopata. Relato de caso
Keywords: Anesthetic techniques, Regional: spinal block; Diseases, Cardiac; Position: exaggerated lithotomy; Surgery, Gynecological, vaginal hysterectomy